Spatial distribution of the nymphs of Jacobiasca lybica (Hemiptera: Cicadellidae) in a vineyard in Andalucia, Spain - RAMÍREZ-DÁVILA, JOSÉ FRANCISCO; PORCAYO-CAMARGO, ELVIA (Revista Colombiana de Entomología, 2008)
The spatial distribution of nymphs of the green mosquito Jacobiasca lybica was determined over one year in an irrigated plot in Cadiz, Spain. The results showed that populations of nymphs within the study area had an aggregated distribution, forming several centers of aggregation, a fact corroborated by maps produced through Kriging. The infestation was not uniform and it was possible to detect a spatial-temporal stability in nymphal populations. It was also determined that it is possible through the techniques of precision agriculture to reduce economic and environmental costs.